Checklist of the freshwater fishes of Colombia: a Darwin Core alternative to the updating problem - Carlos DoNascimiento; Edgar Esteban Herrera-Collazos; Guido A. Herrera-R.; Armando Ortega-Lara; Francisco A. Villa-Navarro; José Saulo Usma Oviedo; Javier A. Maldonado-Ocampo (ZooKeys, 2017)
The present work is part of a process to create a Catalogue of the Freshwater Fishes of Colombia and consisted in the depuration and updating of the taxonomic and geographic components of the checklist of the freshwater fishes of Colombia. An exhaustive revision of the 1435 species recorded in 2008 was necessary to: 1. Add new species described since 2009 and species originally described from Colombia but inadvertently omitted in 2008; 2. Add new records of already described species; 3. Delete species whose presence in Colombia was not supported by voucher specimens in ichthyological collections; and 4. Revise the geographic distribution of the species listed in 2008. This process resulted in the following numbers: 1. Total number of freshwater fish species in Colombia: 1494; 2. Number of species recorded by hydrographic region - Amazon: 706, Orinoco: 663, Caribbean: 223, Magdalena-Cauca: 220, Pacific: 130; and 3. Number of endemic species: 374 (76% from the trans-Andean region). Updating the current checklist is a fundamental requirement to ensure its incorporation in the decision-making process with regard to the conservation of Colombian aquatic species and ecosystems, which are facing transformation processes as a result of activities such as mining, construction of hydroelectric plants, expansion of the agricultural frontier and subsequent deforestation, industrial and domestic pollution, development of waterways, introduction of exotic species, and climate change.